Impact of social isolation on the level of physical activity in young Brazilian athletes caused by COVID-19 - da Silva, L. F.; de Almeida-Neto, P. F.; BulhÕes-Correia, A.; de Queiros, V. S.; Matos, D. G.; Silva Dantas, P. M.; de Araujo Tinoco Cabral, B. G. (The Journal of Sports Medicine and Physical Fitness, 2021)
Social detachment to prevent the spread of the COVID-19 pandemics in the year 2020 can significantly contribute to the physical inactivity of citizens worldwide. The study aimed to analyze the level of physical activity by identifying the training methods used during the social isolation resulting from the COVID-19 pandemic. Sixty-eight Brazilian athletes (both sex, 14.7 ± 1.68 years) answered and adapted the International Physical Activity Questionnaire (I-PAQ) through an online platform. Participants were asked to report their level of physical activity before and during the period of social distance. 67.7% of the interviewed athletes said they were able to adapt their sports training to the isolation environment under the guidance of a distance physical education professional. Only 4.38% of the sample was not training under such supervision and, therefore, inactive. Among the activities performed in the isolation environment, calisthenics was the primary practice (Effect Size: ƒ2 = 0.50, p <0.0001) and the sport practiced at home was the secondary practice (Effect Size: ƒ2 = 0.27, p = 0.004). During the pandemic, the training hours of athletes reduced significantly from ~ 3h to ~ 1h per day (Effect size: 1.74, p <0.0001), as well as, the perceived intensity decreased from "high" to "moderate" (Effect size: 1.38, p <0.0001). The weekly training frequency decreased from ~ 6 to 7 days to ~ 3 to 5 days (Effect size: 0.40, p = 0.03). Therefore, despite the social distance and the reduced pace of training, the young Brazilian athletes analyzed managed to remain physically active during the COVID-19 pandemic.